38.8k views
3 votes
Solve for X in this equation

Solve for X in this equation-example-1

2 Answers

6 votes

Answer: x=e

Explanation:

x= ln(e^e)

using ln(e^x)= x x ln (e), transform the expression

x= e x ln (e)

the natural logatithm of e equals 1

x=e x 1

any expression multiplied by 1 remains the same

x=e alternative form: x= 2.71828

User Ozeray
by
5.0k points
5 votes

ANSWER


x = e

EXPLANATION

The given logarithmic equation


x = ln_(e)(e)

Note that


ln(e) = 1

Using the power rule of logarithms,


x =e \ln(e)

This gives us:


x =e (1)

Simplify to get:


x = e

User Knowbody
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.